Technology Strategy and Competitiveness in Developing Nations: Exploratory Evidence from Nigerian Telecommunication Market / Aminu Ahmad, Hartini Ahmad and Seember Nyager - Aminu, Ahmad; Hartini, Ahmad; Seember, Nyager (Faculty of Business and Management ; UiTM Press, 2009)
While direct link between technology strategy and competitiveness have been established there is dearth of quantitative research on the relative influence of key technology strategy constructs. Similarly although technology strategy is more daunting in developing countries most literatures predominantly focused on developed nations. Against this background scales were source from literature and focus group analysis. Principal component factoring and principal factor axis was run on 157 valid responses from Nigerian telecommunication industry to explore and confirmed the unidimensionality of the constructs. In addition, reliability analysis and constructs correlation provides evidence for constructs validity. Result indicates technology strategy significantly explained the variance on organizational competitiveness.Furthermore Beta coefficients indicate training, maintenance & exploitation policy (TMEP) is the most important driver of competitiveness reinforcing the need for skillful manpower and internal infrastructure to accommodate new acquisitions in technology strategy. Finally theoretical and managerial implications of the research findings were highlighted